Azerbaijan : The Role of Higher Education in Innovation - World Bank Group (World Bank, Washington, DC, 2019)
As the push to engage in the global knowledge economy becomes increasingly vital to countriesaround the world, higher education institutions (HEIs) are being recognized as valuable centers for research and teaching in support of entrepreneurship, innovation, competitiveness, and economic growth. Many HEIs in Azerbaijan, however, lack the capacity to serve as effective dynamic hubs for such enterprising efforts, limiting Azerbaijan’s ability to collaborate and compete with other nations in the global economy. Leveraging its expertise in this area, the World Bank carried out an analysis of the status of the research and innovation environment in Azerbaijan’s higher education sector, identifying the main obstacles to the advancement of research work and its results and to effective coordination between higher education institutions and industry to achieve innovation-led growth. Science in Azerbaijan is examined through policy and institutional lenses, encompassing its governance, funding and management issues. The analysis looks at innovation as a dynamic outcome from university-industry collaboration, examining issues of technology transfer and intellectual property rights, the start-up environment, and funding of research toward practical and applied outcomes. The results of the analysis presented in this note, based on national and international data sources along with numerous consultations with a variety of stakeholders, informs concrete policy measures that can be taken by Azerbaijani authorities to strengthen the capacity of HEIs to serve as key actors in the country’s innovation ecosystem and facilitate economic diversification within the global knowledge economy. Recently adopted national strategic documents are creating possibilities for reform by the MOE as well as by individual HEIs. The Education Development Strategy (EDS), approved by the President of the Republic of Azerbaijan in 2013, defines purposeful reforms in education with the main goal of building a competitive and leading education system in line with the world’s best practices and based on cutting-edge technology infrastructure, quality and accessibility. The key findings and recommendations center on undertaking strategic efforts to maximize the quality and relevance of higher education as it relates to innovation and economic competitiveness.